Антология выдающихся достижений в науке и технике. Часть 1: открытие периодического закона химических элементов - Баранов, М.И. (Електротехніка і електромеханіка, 2011)
A brief outline from the history of discovery of the basic fundamental law of nature, Mendeleev law, that reveals essential intrinsic secrets of the universe, is given.